1994
DOI: 10.1507/endocrj.41.579
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Pit-1 mRNA Is Not Required for the Estrogen-Induced Expression of Prolactin Gene and Lactotroph Proliferation.

Abstract: Abstract. Estrogen has been shown to stimulate lactotroph proliferation and expression of the prolactin (PRL) gene. Recently it has been established that Pit-1, a pituitary-specific transcription factor, is required for lactotroph proliferation.Furthermore, in vitro studies showed that an increase in the PRL promoter activity caused by estrogen was dependent of the amount of cotransfected Pit-l-expressing plasmid. These findings led us to examine whether the induction of Pit-1 mRNA is required for the estrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…We used a retrovirus bearing the human Ret‐S cDNA (LPC‐Ret) or the empty construct (LPC). For retroviral expression, we needed actively dividing cells, and so we used estrogen‐induced lactotroph hyperplasia (Tsukahara et al , 1994). The LPC or LPC‐Ret retrovirus was delivered to estrogen‐injected female rats by stereotaxic injection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a retrovirus bearing the human Ret‐S cDNA (LPC‐Ret) or the empty construct (LPC). For retroviral expression, we needed actively dividing cells, and so we used estrogen‐induced lactotroph hyperplasia (Tsukahara et al , 1994). The LPC or LPC‐Ret retrovirus was delivered to estrogen‐injected female rats by stereotaxic injection.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is no substantial in vivo evidence in rodents or humans to support this latter possibility: the Pit‐1 gene is not altered in adenomas, and Pit‐1 expression appears to be more closely related to GH secretion than to tumorigenesis (Delhase et al , 1993; Hoggard et al , 1993; Pellegrini et al , 1994). Moreover, Pit‐1 mutations have been found in human hypopituitarism without pituitary hypoplasia (Pfaffle et al , 1992), whereas no increase in Pit‐1 expression is required for in vivo estrogen‐induced lactotroph hyperplasia in rats (Tsukahara et al , 1994). Our data show that too much Pit‐1 is deleterious for the somatotroph; conversely, knocking down Pit‐1 prevents apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Soybeans may also be estrogenic, resulting in their ability to stimulate the synthesis and secretion of PRL and GH. On the other hand, Tsukahara et al (1994) suggested that an increase in Pit-1 mRNA was not required for estrogen-induced lactotroph proliferation or PRL gene expression. In addition, Son et al (2001) suggested that isoflavones in soybeans may not be responsible for the synergistic goitrogenic effect of soybeans and iodine deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for the finding of no difference of Pit-1 mRNA but greater pituitary PRL mRNA in OSe vs. ISe steers could be that although Pit-1 is indispensable for prolactin production, an increase in Pit-1 mRNA is not necessary to promote PRL gene expression. For example, in estrogen-treated rats, lactotroph proliferation and enhanced expression of PRL mRNA but not an increase in Pit-1 mRNA have been observed (Tsukahara et al, 1994).…”
Section: Ose Form Of Se Supplementation Had Greatermentioning
confidence: 99%